Health Monitoring of An Existing RC Structure Considering Seismic Analysis Using Analysis Tools Staad : A Review - Abhishek Sharma; Pradeep Kumar Nirmal; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2021)
Seismic assessment of an existing structure which is not designed as per seismic criterias are not considered safe during natural disaster which can cause loss of life and property. Therefore it can be consider as an important point to be considered during redesigning or retrofitting of the structure. In this paper we are reviewing literatures presented by different authors around the world related to retrofitting and seismic assessment of existing structures.
Keywords: Seismic Assessment; Staad.pro; Forces; Displacement; Strength; Rebound Hammer; Retrofitting